(untitled) (Archive of Conferences, 2021)
Pedagogical competence is considered as a factor in ensuring the quality of teaching. Today it is important to study the criteria for determining the competence of a teacher. The article introduces the concepts of competence and competence, the similarities and differences between them. The types of professional pedagogical competencies are defined. The stages of formation of pedagogical competence are described.